Uji Laboratorium: Analisis Nilai Filtrat High Pressure Water Based Mud pada Sumur Sunset - Hutabarat, Romauli Tiurma; Fathan, Muhammad Rizqie; Ulfah, Baiq Maulinda (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Drilling mud filtration plays an important role in maintaining wellbore stability and preventing excessive fluid loss during the drilling process. If uncontrolled, filtration can damage formations and disrupt operations. This study discusses the effectiveness of High-Pressure Water-Based Mud (HPWBM) with the addition of CaCo3 and Fracseal as an effort to reduce filtration and form a good mud cake. The purpose of this study is to evaluate the filtration performance of HPWBM in various well sizes under HighPressure High-Temperature (HPHT) conditions. This test was conducted in accordance with API standards ( 10 ml/30 minutes). The results show that the filtration rate for the 26“ trajectory is 4.6 ml/30 minutes, the 17-1/2” trajectory is 3.8 ml/30 minutes, the 12-1/4“ trajectory is 4.0 ml/30 minutes, and the 8-1/2” trajectory is 2.4 ml/30 minutes. All values were below the API limit, with a decreasing trend at greater depths. This study confirms that HOWBM with CaCo3 and Fracseal can control filtration, maintain well stability, and improve drilling efficiency and safety.